Implementation of Comprehensive Geriatric Assessment in Elderly-Friendly Public Health Centers and General Public Health Centers in Bandung - Astri Keli; Sharon Gondodiputro; Nita Arisanti (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Comprehensive Geriatric Assessment (CGA) is a comprehensive, multi-dimensional biopsychosocial examination. The CGA is conducted at the primary health facility such as the public health centers (Pusat Kesehatan Masyarakat, Puskesmas); categorized as Eldery-Friendly Public Health Centers (Puskesmas Santun Lansia), a puskesmas where one of its programs provides health care for the elderly, and Puskesmas in general, where there is no specific program for the elderly. The purpose of the study was to analyze the difference between Puskesmas santun lansia and Puskesmas in providing CGA.Methods: A comparative analytical study was carried out from August to November 2019, involving Puskesmas Santun Lansia (n=6) and puskesmas (n=12) in Bandung City. From each Puskesmas, two elderly were selected and observed for the CGA. The assessment consisted of the identity of the elderly, anamnesis, vital sign examination, physical examination, assessment of nutritional status, functional, psychosocial, social, cognitive, and mental assessment. The collected data were analyzed using the Chi-square or Fisher’s exact test.Results: This study showed that there was no difference between Puskesmas Santun Lansia and Puskesmas in the CGA, except in the simple nutritional anamnesis (p=0.003), anamnesis of the symptoms or signs of the dysfunction of the organ system (p=0.034), and body mass index measurement (p=0.009).Conclusions: The CGA is not well implemented in both Puskesmas. In the future, both of the Puskesmas should enhance their knowledge and skills to provide the CGA as mentioned in the regulation of the Minister of Health No. 67/2015.